Nuclear reactions in the storage ring ESR with EXL. (June 2016) - Kröll, Th; von Schmid, M; Zamora, J C; Bagchi, S; Bönig, S; Csatlós, M; Dillmann, I; Dimopoulou, C; Egelhof, P; Eremin, V; Furuno, T; Geissel, H; et al.
Abstract: The EXL project aims to study nuclear structure by direct reactions in inverse kinematics at the storage rings of the future FAIR facility. In this contribution, we present the status of the project: the technical implementation at the ESR at GSI and preliminary results of the EXL campaign in 2012, the first using also a radioactive beam.